(untitled) (Economics and region, 2017)
The genesis and evolution of the formation of agglomeration and their impact on ensuring sustainable development in Ukraine were investigated. Criteria and the main features of agglomeration in the structure and components of sustainable development were disclosed. It is noticed that the main task of the forming agglomeration is to help to improve the living standards of residents of settlement remote from the city-core of agglomeration and equalization of differences in social and cultural services to the population. A number of measures were offered to accelerate the process of providing sustainable development. Among the latest, the development of mechanisms for attracting investments in the development of the social sphere and increasing the efficiency of their usage may provide positive effect.